Evaluation on discomfort level among students using desks in classrooms - Mahmood, Ali; Mohd Sapuan, Salit; Karmegam, Karuppiah; Abu Saleh, Ahmed (Penerbit UTM Press, 2015)
This study was conducted to evaluate the discomfort level among students using desks in classrooms of Polytechnic Kuching. The students (n=500) completed the questionnaire survey form using Borg’s CR-10 Scale showing body chart discomfort. The students was asked to identify their body areas experiencing discomfort and to rate this discomfort on a score rating groups (0 to 5). Score 0-1.99 = No discomfort (1), score 2.00-3.99 = Discomfort (2) and score 4.00-5.00 = Very uncomfortable (3). The evaluation of the seating shows discomfort level of students and any outstanding problems arising. Students were asked to rank in the order of 10 statements about comfort and choose three responses which gave the most consistent equal interval scale. The results in that the main response of discomfort indicated the students mostly agree that they are feeling from cramped, stiff, numb, sore and tender to unbearable pain, barely comfortable and feel uncomfortable. The project was identified to evaluate the comfort level of classrooms desks for polytechnic students. Overall, there was a significant discomfort level for the students whilst using the desks and a possible solution put forward is to design a new type of classroom desk made of natural fibre reinforced composite.